Penulisan Buku Perjalanan Al-Qur’an Tua di Bumi Persaudaraan, Dakwah Kesultanan Ternate di Alor - Rahmad Nasir; Abdullah R S (Jumat Keagamaan: Jurnal Pengabdian Masyarakat, 2021)
There are not many scientific texts comprehensively containing the history of the entry of Islam in Alor district, especially from the Sultanate of Ternate, besides that there are not many Islamic Religion teachers in Madrasas who teach students about this. Even the lessons of Islamic Cultural History (SKI) that are taught are also very general in nature which are taught throughout Indonesia and even in the world. Meanwhile, the discussion of Special SKI conditions in Alor Regency seems to be rare. It is also difficult to find preachers / missionaries conveying in religious pulpits. Among the thirst of the Alor community, especially Alor Muslims for the identity of Islam in Alor, the service team tried to carry out service activities for writing the book "Journey of the Old Qur'an in the Brotherhood Earth, Da'wah of the Sultanate of Ternate in Alor" (“Perjalanan Al-Qur’an Tua di Bumi Persaudaraan, Dakwah Kesultanan Ternate di Alor”) which involved STKIP Muhammadiyah Kalabahi campus, Ministry of Education and Culture. Religion of Alor Regency and Alor Regency Government as well as speakers/resources. The subject of the service program is the people of Alor Regency, especially Muslims in Alor Regency. The data were obtained through the Focup Group Discussion (FGD) and Seminar forums, scripts from speakers/resources, observations to Islamic heritage sites in Alor. The type of data obtained is qualitative data in the form of manuscripts of speakers / resource persons and documentation of historical sites. The way to analyze it is by triangulating data based on data collection methods, extending the search time and comparing data sources. The important findings are the truth claims of each village/tribe/sub-tribe in their respective versions, the preachers of Ternate namely Gogo and Likur headed to Alor using a sea ark, the missionaries spread Islam peacefully through a persuasive approach to local rulers/kings and its people, through marriage/marriage of local communities, and other soft approaches so that it can be accepted and developed quite well in Alor district. This service activity was a bit of a challenge, but thanks to the support of various parties, the book was finally published and widely distributed even outside NTT.